1994
DOI: 10.1007/bf00185769
|View full text |Cite
|
Sign up to set email alerts
|

Mitral cell dendrites: a comparative approach

Abstract: Phylogenetically persistent structures such as the mitral cells of the vertebrate olfactory bulb undergo changes in their dendritic arbor in the course of evolution. The morphology of mitral cells and the main elements of the olfactory bulb circuit in all classes of vertebrates are reviewed in this paper. Most of the neuronal elements found in the mammalian olfactory bulb are present in anamniotes. However, in contrast to those of amniotes, the mitral cells of most anamniotes lack basal dendrites, and periglom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 121 publications
2
56
0
Order By: Relevance
“…The growth of these arbors occurs by addition of new dendritic segments that "fill in" existing territory, as well as at the perimeter of the tree, thus widening its reach. Such scaling growth of dendritic arbors in relation to body size is a widespread phenomenon and has previously been observed in different types of nerve cells, including Purkinje, pyramidal, olfactory mitral cells and sympathetic ganglionic neurons (3,4,52,53).…”
Section: Discussionmentioning
confidence: 74%
“…The growth of these arbors occurs by addition of new dendritic segments that "fill in" existing territory, as well as at the perimeter of the tree, thus widening its reach. Such scaling growth of dendritic arbors in relation to body size is a widespread phenomenon and has previously been observed in different types of nerve cells, including Purkinje, pyramidal, olfactory mitral cells and sympathetic ganglionic neurons (3,4,52,53).…”
Section: Discussionmentioning
confidence: 74%
“…rabbit and turtle [Mori et al 1981[Mori et al , 1983) and thus combine inputs with different chemical sources. Such patterns are common in lower vertebrates (Dryer & Graziadei 1994, Nieuwenhuys 1967 and in the AL of many insects (e.g. locusts and wasps) (Laurent 1996, Masson & Mustaparta 1990 (Dryer & Graziadei 1994).…”
Section: Lateral Connections Within the Olfactory Bulb/antennal Lobe mentioning
confidence: 91%
“…Such patterns are common in lower vertebrates (Dryer & Graziadei 1994, Nieuwenhuys 1967 and in the AL of many insects (e.g. locusts and wasps) (Laurent 1996, Masson & Mustaparta 1990 (Dryer & Graziadei 1994). GC-mediated pathways may indeed link M/TCs whose somata and input glomeruli lie millimeters apart (Shipley & Ennis 1996).…”
Section: Lateral Connections Within the Olfactory Bulb/antennal Lobe mentioning
confidence: 96%
See 1 more Smart Citation
“…Odor information transfer from the olfactory bulb to higher brain centers It has been long believed that MCs in teleost fishes typically have multiple primary dendrites innervating multiple glomeruli ( Dryer and Graziadei, 1994). However, a recent study (Fuller et al, 2006) reported a revised description of zebrafish MC morphology in which the majority of retrogradely labeled MCs have a single primary dendrite with a discrete tuft and a smaller proportion of MCs showing the multidendritic morphology also innervates a single glomerulus.…”
Section: Heterogeneity Of Mitral Cellsmentioning
confidence: 99%